From Bricks to Bytes: Digitizing Green Cities - Diane Valerie Wildsmith; Phil Smith (International Journal of Technology, 2014)
The research is focused on green cities and the role of digital media in the development of corporate sponsorship for high tech green cities currently under construction (e.g., Masdar in Abu Dhabi, Songdo in South Korea, PlanIT Valley in Portugal). The urban imaginary of virtual green cities is linked to an ecological cyberspace that promotes futuristic images of green cities, such as Vincent Callebaut’s Hydrogenase (2010)—a transport hub for an algae farm and biohydrogen airships. These images of sustainable green cities pose a challenge to defining ecological civic space and green architecture, especially in the transformation of Jakarta into an eco-architectural hub that balances social, economic, and environmental issues. The role of Google Earth and digital maps must not be underestimated in digitizing the “bytes” and realizing design scenarios for the “bricks” of green cities, including those options related to traffic planning simulations, water catchment scenarios, disaster/flood planning, and social media simulation for crowd control and governance issues.